Expression cloning of a human polysialyltransferase that forms the polysialylated neural cell adhesion molecule present in embryonic brain. - Nakayama, J (1995)
Polysialic acid is a developmentally regulated posttranslational modification of the neural cell adhesion molecule (N-CAM). It has been suggested that this large anionic carbohydrate modulates the adhesive property of N-CAM, but the precise function of polysialic acid is not known. Here we describe the isolation and functional expression of a cDNA encoding a human polysialyltransferase. For this expression cloning, COS-1 cells were cotransfected with a human fetal brain cDNA library and a cDNA encoding human N-CAM. Transfected COS-1 cells were stained with a monoclonal antibody specific for polysialic acid and enriched by fluorescence-activated cell sorting. Sibling selection of recovered plasmids resulted in a cDNA clone that directs the expression of polysialic acid on the cell surface. The deduced amino acid sequence indicates that the polysialyltransferase shares a common sequence motif with other sialyltransferases cloned so far. The polysialyltransferase is, however, distinct by having two clusters of basic amino acids. The amount of the polysialyltransferase transcripts correlates well with the formation of polysialic acid in various human tissues, and is abundant in the fetal brain but not in the adult brain. Moreover, HeLa cells stably expressing polysialic acid and N-CAM promoted neurite outgrowth and sprouting. These results indicate that the cloned polysialyltransferase forms polysialylated, embryonic N-CAM, which is critical for plasticity of neural cells.